2020
DOI: 10.3348/jksr.2020.81.3.488
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer Dementia and Microvascular Pathology: Blood-Brain Barrier Permeability Imaging

Abstract: 최근의 연구들은 알츠하이머병의 병리가 단순히 아밀로이드와 타우단백질의 축적만이 아닌, 혈액뇌장벽(blood brain barrier; 이하 BBB) 이상과 같은 미세혈관병리와 밀접한 관련이 있음을 밝히고 있다. BBB 투과도 변화는 아밀로이드 및 타우 단백질 축적뿐 아니라 신경염증과 신경 퇴행성변화를 일으킴으로써 결국 임상 치매를 야기한다. 최근에는 알츠하이머 및 관련 질환의 BBB 이상을 보기 위한 MR 영상의 이용이 증가하고 있다. 이 종설에서는 알츠하이머병에서 BBB와 관련된 병리를 소개하고, BBB 투과도 변화에 대한 MR 영상 연구들을 소개할 것이다. 또한 BBB 투과도 측정을 위한 MR 방법론 개요와 문제점들을 제시할 것이다.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Although the pathogenesis of many neurodegenerative and cerebrovascular diseases remains unclear, blood-brain barrier (BBB) breakdown and leakage have been implicated in their mechanism [ 1 2 3 ]; the relationship between BBB permeability and neurodegenerative diseases has thus garnered increasing attention [ 4 ]. Studies have reported that BBB breakdown is associated with rapid cognitive decline [ 5 ] and contributes to cognitive impairment independent of Alzheimer's disease biomarkers [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of many neurodegenerative and cerebrovascular diseases remains unclear, blood-brain barrier (BBB) breakdown and leakage have been implicated in their mechanism [ 1 2 3 ]; the relationship between BBB permeability and neurodegenerative diseases has thus garnered increasing attention [ 4 ]. Studies have reported that BBB breakdown is associated with rapid cognitive decline [ 5 ] and contributes to cognitive impairment independent of Alzheimer's disease biomarkers [ 6 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging findings of microvascular pathology, also known as a SVD in AD, include lacunes, WMH, cerebral microbleed, and enlarged perivascular spaces (ePVSs). 11 Among them, WMH is the most widely investigated and validated for SVD marker until now. WMH is also an imaging factor that is correlated with cognitive aging and AD.…”
Section: Neuroimaging Test: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…This distribution is determined based on several physiological indicators, such as arterial input function, which is one of the least affected indicators by imaging conditions or imaging techniques. 11 …”
Section: Neuroimaging Test: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%